Depression and suicidal ideation in elderly institutionalized and non-institutionalized in Portugal - Almeida, Lurdes (2012)
Introduction/Objectives: Depression has shown as the more common mental disorder in elderly community and suicide is it worst consequence. In the Portuguese context suicide rates among the elderly take values higher than in other age groups. The present study aimed to compare elderly institutionalized and not institutionalized in terms of depression, suicidal ideation, dependency and leisure activities. Material and Methods: The sample was collected in Algarve, Alentejo and Lisbon, in 155 elderly, 85 institutionalized and 71 not institutionalized, with similar proportions between genders. The instruments were The Activity and Leisure Index (IAL), the Geriatric Depression Scale (GDS), The Barthel Index and the Beck Scale for Suicide Ideation (BSI). Results: The results showed that the elderly institutionalized did not presented higher depression, loneliness, suicidal thoughts or lowest level of activity and leisure, but were less independent. The participants with highest suicidal thoughts had more depression. A self-perception of worse health and more loneliness were related with more depression. A higher activity and leisure was related with less suicidal ideation. Conclusions: The data seem to show that the institutionalization of elderly is not related negatively with depression and suicidal ideation.